Characteristics of Bumiputera entrepreneurs in non-wood industrty - Zulkifli, Zharif Ashraf (2018)
Non-wood industry is an industry that has been in Malaysia for a long time. This industry has helped Bumiputera entrepreneurs in providing profit to them and at the same time uplift our country’s economy. This research is conducted to find Key Success Factor (KSF) from Bumiputera entrepreneurs in this non-wood industry. A total of 57 questionnaires were distributed but only 38 Bumiputera entrepreneurs responded within a period of four months. The result shows that success factor is important to improve their product performance. This research involved five main factors which are management, financial, marketing, technology and human resource. The research is conducted in Peninsular Malaysia, involving states such as Selangor, Johor, Kelantan and Malacca. The research utilized Score Analysis which covers five main contexts in research objective. According to Score Analysis Method, management is placed in top position while technology is ranked last. This is because management is the key factor among all the other factors while technology is placed last because Bumiputera entrepreneurs need more manpower than technology in the process of product production. Management factor is the most important basic factor in ensuring Bumiputera entrepreneurs succeed in non-wood industry.